Modeling of Forming a Nanoporous Structure of Carbon Materials for Electrodes of Electrochemical Capacitors - Ostafiychuk, B.K.; Lyubun, Z.M.; Lisovskiy, R.P.; Moiseienko, M.I.; Rachiy, B.I.; Ivanichok, N.Ya.; Bandura, Kh.V. (Physics and Chemistry of Solid State, 2020)
The paper presents the results of predicting the physical properties of nanoporous carbon materials during synthesis with their subsequent use as an electrode material for electric double-layer capacitors. It has been established a multilayer neural network can be used to predict the sorption properties of nanoporous carbon materials. A multilayer neural network confirms the experimental dependences of the characteristics of nanoporous carbon materials porous structure on the technological conditions of its obtaining.